Post-Thaw Characteristics of the Simmental Sperm Function in Different Ages of Bulls - F. A. Satrio; N. W. K. Karja; M. A. Setiadi; E. M. Kaiin; M. Gunawan; B. Purwantara (Faculty of Animal Science, Bogor Agricultural University, 2022)
This study aims to determine the effect of the age difference of Simmental bulls on motion characteristics, capacitation status, and DNA fragmentation of post-thawing sperms. The frozen semen used was collected from twelve bulls, which were divided into four groups of age, which include a group of two, four, ≥ 10 years old with high semen rejection (≥ 10 HR), and ≥ 10 years old with low semen rejection (≥ 10 LR). Computer Assisted Sperm Analysis (CASA) was used to determine sperm motion characteristics, capacitation status by chlortetracycline (CTC) staining, plasma membrane integrity, and viability using eosin-nigrosine staining. In contrast, the DNA fragmentation index was determined using the Sperm-Bos-halomax kit. The results showed that the four year old group had a higher total and progressive motility percentage than the others (p<0.05). In all groups, there was no significant difference among sperm kinematics such as VAP, VSL, VCL, STR, and ALH. However, the LIN, WOB, and BCF of the ≥ 10 HR year old groups were significantly lower (p<0.05) than those of the other groups. However, un-capacitated sperm was higher (p<0.05) in the two years and four years old groups compared to the ≥ 10 years old, while the four years old group had lower capacitated and acrosome-reacted (p<0.05) than the other groups. Furthermore, the sperm membrane integrity, viability, and DNA fragmentation index of the ≥ 10 years old groups were significantly higher (p<0.05) than those of the other groups. The research concludes that aging in the Simmental bull affects motion characteristics, capacitation status, and DNA fragmentation of post-thawing sperm. However, the semen rejection rate in the older bull did not directly affect the post-thawing sperm quality.